2014
DOI: 10.1371/journal.pone.0105016
|View full text |Cite
|
Sign up to set email alerts
|

Overlapped Sequence Types (STs) and Serogroups of Avian Pathogenic (APEC) and Human Extra-Intestinal Pathogenic (ExPEC) Escherichia coli Isolated in Brazil

Abstract: Avian pathogenic Escherichia coli (APEC) strains belong to a category that is associated with colibacillosis, a serious illness in the poultry industry worldwide. Additionally, some APEC groups have recently been described as potential zoonotic agents. In this work, we compared APEC strains with extraintestinal pathogenic E. coli (ExPEC) strains isolated from clinical cases of humans with extra-intestinal diseases such as urinary tract infections (UTI) and bacteremia. PCR results showed that genes usually foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
130
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(145 citation statements)
references
References 38 publications
13
130
0
2
Order By: Relevance
“…The majority of the sequence types (ST10, ST57 ST 224, ST354 and S624) identified in the current study from FQ and ESC resistant isolates have been previously described and are globally distributed amongst humans as well as animals (Fernandes et al, 2016;Kim et al, 2011;Maluta et al, 2014;Sola-Gines et al, 2015;Zhao et al, 2014). ST2705 and ST6053 are host restricted and have been previously isolated from poultry and wild birds (Dahms et al, 2015;Day et al, 2016;Jones-Dias et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The majority of the sequence types (ST10, ST57 ST 224, ST354 and S624) identified in the current study from FQ and ESC resistant isolates have been previously described and are globally distributed amongst humans as well as animals (Fernandes et al, 2016;Kim et al, 2011;Maluta et al, 2014;Sola-Gines et al, 2015;Zhao et al, 2014). ST2705 and ST6053 are host restricted and have been previously isolated from poultry and wild birds (Dahms et al, 2015;Day et al, 2016;Jones-Dias et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
“…The current study reported a variation in the ST among the clinical FQ resistant isolates (keeping in mind that there was only two clinical FQ resistant isolates) with one assigned as ST224 while the other was ST10. Both STs have previously been identified in horses, dogs, buffalos and human pathogenic and non-pathogenic E. coli Aizawa et al, 2014;Dissanayake et al, 2014;Maluta et al, 2014;Manges and Johnson, 2012;Pires-dos-Santos et al, 2013;Vignaroli et al, 2012;Zhao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations